Antenatal care presentation and engagement in the context of sex work: exploring barriers to care for sex worker mothers in South Africa - Lauren Parmley; Amrita Rao; Zamakayise Kose; Andy Lambert; Ryan Max; Nancy Phaswana-Mafuya; Mfezi Mcingana; Harry Hausler; Stefan Baral; Sheree Schwartz (BMC, 2019)
Abstract Background Late presentation combined with limited engagement in antenatal care (ANC) increases risk of vertical transmission among mothers living with HIV. Female sex workers (FSW) have more than four times greater burden of HIV than other women of reproductive age in South Africa and the majority of FSW are mothers. For mothers who sell sex and are at increased HIV acquisition risk, timely and routine ANC seeking is especially vital for prevention of vertical transmission. This study represents a mixed-methods study with FSW in Port Elizabeth, South Africa, to characterize factors influencing ANC seeking behaviors in a high HIV prevalence context. Methods FSW (n = 410) were recruited into a cross-sectional study through respondent-driven sampling between October 2014 and April 2015 and tested for HIV and pregnancy. A sub-sample of pregnant and postpartum women (n = 30) were invited to participate in in-depth interviews (IDIs) to explore their current or most recent pregnancy experiences. IDIs were coded using a modified grounded theory approach and descriptive analyses assessed the frequency of themes explored in the qualitative analysis among the quantitative sample. Results In the quantitative survey, 77% of FSW were mothers (313/410); of these, two-thirds were living with HIV (212/313) and 40% reported being on antiretroviral therapy (ART) (84/212). FSW in the qualitative sub-sample reported unintended pregnancies with clients due to inconsistent contraceptive use; many reported discovering their unintended pregnancies between 4 and 7 months of gestation. FSW attributed delayed ANC seeking and ART initiation in the second or third trimesters to late pregnancy detection. Other factors limiting engagement in ANC included substance and alcohol use and discontent with previous healthcare-related experiences. Conclusions Late pregnancy discovery, primarily because pregnancies were unplanned, contributed to late ANC presentation and delayed ART initiation, increasing risks of vertical HIV transmission. Given limited ART coverage among participants, addressing the broader sexual and reproductive health and rights needs of mothers who sell sex has important implications for preventing vertical transmission of HIV. Integrating comprehensive family planning services into FSW programming, as well as providing active linkage to ANC services may reduce barriers to accessing timely ANC, decreasing risks of vertical transmission.